Adherence to clinical practice guidelines (CPGs) for the treatment of cancers in Australia and the factors associated with adherence: a systematic review protocol - Frances Rapport; Jeffrey Braithwaite; Kristiana Ludlow; Yvonne Tran; Mia Bierbaum; Gaston Arnolda; Bróna Nic Giolla Easpaig (BMJ Open, 2021)
Introduction Clinical practice guidelines (CPGs) synthesise the latest evidence to support clinical and patient decision-making. CPG adherent care is associated with improved patient survival outcomes; however, adherence rates are low across some cancer streams in Australia. Greater understanding of specific barriers to cancer treatment CPG adherence is warranted to inform future implementation strategies.This paper presents the protocol for a systematic review that aims to determine cancer treatment CPG adherence rates in Australia across a variety of common cancers, and to identify any factors associated with adherence to those CPGs, as well as any associations between CPG adherence and patient outcomes.Methods and analysis Five databases will be searched, Ovid Medline, PsychInfo, Embase, Scopus and Web of Science, for eligible studies evaluating adherence rates to cancer treatment CPGs in Australia. A team of reviewers will screen the abstracts in pairs according to predetermined inclusion criteria and then review the full text of eligible studies. All included studies will be assessed for quality and risk of bias. Data will be extracted using a predefined data extraction template. The frequency or rate of adherence to CPGs, factors associated with adherence to those CPGs and any reported patient outcome rates (eg, relative risk ratios or 5-year survival rates) associated with adherence to CPGs will be described. If applicable, a pooled estimate of the rate of adherence will be calculated by conducting a random-effects meta-analysis. The systematic review will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Ethics and dissemination Ethics approval will not be required, as this review will present anonymised data from other published studies. Results from this study will form part of a doctoral dissertation (MB), will be published in a journal, presented at conferences, and other academic presentations.PROSPERO registration number CRD42020222962.